Long segment ureterectomy with tapered demucosalized ileum replacement of ureter for ureteral cancer: a case report and literature review - Xie, Zhifei; Liu, Mingwen; Chen, Shulian; Tang, Wen; Liang, Guobiao; Xu, Jingyu; Zhao, Zeju (Frontiers in Oncology, 2024)
Radical nephroureterectomy (RNU) with bladder sleeve resection is currently the gold standard for the treatment of high-risk ureteral cancer. However, in certain special cases, such as bilateral upper tract urothelial carcinoma （UTUC）, isolated and chronic kidney disease, and low-risk UTUC, kidney sparing surgery（KSS）may represent a viable alternative, though it remains highly challenging. The current KSS options for ureteral cancer include endoscopic treatment, segmental ureterectomy, total ureterectomy combined with kidney autotransplantation and nephrostomy. These methods are associated with significant disadvantages, such as a high risk of recurrence and vascular-related complications. On the basis of previous studies, we creatively proposed a surgical method of long segment ureterectomy with tapered demucosalized ileum(TDI) replacement of the ureter for ureteral cancer, and successfully performed this operation on a patient with ureteral cancer. The follow-up results showed that this surgical method provides good tumor control while preserving the patient's renal function and improves the inherent defect of the ileal replacement of the ureter, which is a feasible choice for patients with ureteral cancer and kidney preservation.